Pengaruh Mekanisme Corporate Governance Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia 2004-2006 - Nia Yuniarsih (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2013)
The objective of this study is to examine the influence of corporate governance mechanism, namely managerial ownership, institutional ownership, and size of independent commisioner to earnings management. This study takes sample from 74 companies in the manufacturing sector at the Indonesia Stock Exchange, which were published in financial report from 2004-2006. The method of analysis of this research used multi regression and single regression. The results of this study show that (1)managerial ownership had significant influence to earnings management, (2)institutional ownership had significant influence to earnings management, (3) size of independent commisioner had not significant influence to earnings management, (4) simultaneously of managerial ownership, institutional ownership, and size of size of independent commissioner had significant influence to earnings management.